2012
DOI: 10.1159/000330241
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation of the Inflammatory Response Induced by Androctonus australis hector Neurotoxins: Biomarker Interactions

Abstract: Objective:Androctonus australis hector (Aah) is the most dangerous scorpion in the Maghreb countries. Its venom contains three major neurotoxins (Aah I, Aah II and Aah III), which are responsible for almost all the lethal effects caused in mammals. These toxins act on the voltage-gated sodium channels of excitable cells. The targets and the lethal effects of these toxins have been extensively studied. However, their effects on the induced immune response after envenoming have not deeply elicited. We therefore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 61 publications
(29 reference statements)
0
19
0
Order By: Relevance
“…NO plays a role in immunity and inflammation but also in neurotransmission, muscle relaxation, and vasodilatation. An increase of NO levels in the serum or in peritoneal macrophage culture correlated with production of pro-inflammatory cytokines has been shown after experimental and accidental SE (Meki and Mohey El-Dean 1998;Petricevich and Peña 2002;Pessini et al 2006;Zoccal et al 2011;Raouraoua-Boukari et al 2012). These high concentration of NO may be associated with severe conditions, such as septic shock, hypertension, febrile response, and severe SE (Petricevich and Peña 2002;Pessini et al 2006;Petricevich 2010).…”
Section: Oxidative and Nitrosative Stressmentioning
confidence: 99%
See 3 more Smart Citations
“…NO plays a role in immunity and inflammation but also in neurotransmission, muscle relaxation, and vasodilatation. An increase of NO levels in the serum or in peritoneal macrophage culture correlated with production of pro-inflammatory cytokines has been shown after experimental and accidental SE (Meki and Mohey El-Dean 1998;Petricevich and Peña 2002;Pessini et al 2006;Zoccal et al 2011;Raouraoua-Boukari et al 2012). These high concentration of NO may be associated with severe conditions, such as septic shock, hypertension, febrile response, and severe SE (Petricevich and Peña 2002;Pessini et al 2006;Petricevich 2010).…”
Section: Oxidative and Nitrosative Stressmentioning
confidence: 99%
“…These mediators may be derived from macrophages and epithelial cells, but the neutrophil itself is a major source of IL-8. Thus, adherent neutrophils produce and release oxygen free radicals and enzymes, such as proteases (e.g., elastase and metalloproteinases) and myeloperoxidase (MPO), exacerbating damage to endothelial cells and inducing tissue injury after SE (Coelho et al 2007;Adi-Bessalem et al 2012;Raouraoua-Boukari et al 2012). Polymorphonuclear activation and migration is a result of a cascade of cellular events, in which polymorphonuclear and endothelial cells and macrophages act in concert (Fig.…”
Section: Neutrophils and Macrophagesmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathogenesis of these disturbances is multifactorial. In previous studies, it has been reported that A. australis Hector venom and its toxins are able to induce an inflammatory response characterized by high serum levels of cytokines, nitric oxide (NO), cellular peroxidase activities [eosinophil peroxidase (EPO), myeloperoxidase (MPO)], and tissue leucocytosis [14,15,17,18]. …”
Section: Introductionmentioning
confidence: 99%